Atlas of the environment - Lean, Geoffrey (Prentice Hall Press, 1990)
The third edition of this environmental atlas states that its purpose is to show the effect the human species has on nature rather than how nature effects humanity. Each chapter consists of a subject essay covering current problems, economic factors, projections, and possible solutions. In the middle of each essay is a two-page spread with graphics illustrating the points made. There are more than 200 impressive diagrams, maps, pie charts, graphs, and tables in vivid colors that are easy to read and interpret. Some maps have not changed at all since the earlier edition. Others show dramatic changes; for example, the 1990 edition listed Laos as having the fourth-highest percentage of population (72 percent) without access to safe drinking water. In the new edition that figure has dropped to 39 per cent, with Laos eighteenth. Maps in the endpapers reflect the new independent countries of the former Soviet Union. Information for each subject comes from the World Wildlife Fund, the United Nations Environment Programme, the Food and Agriculture Organization, the World Resources Institute, and similar organizations. Since abbreviations for these are used in the maps and diagrams, a list with full organization names would have been helpful.